Environmental and Genetic Factors Involved in Plant Protection-Associated Secondary Metabolite Biosynthesis Pathways - Zhan, Xiaori; Chen, Zhehao; Chen, Rong; Shen, Chenjia (Frontiers in Plant Science, 2022)
Plant specialized metabolites (PSMs) play essential roles in the adaptation to harsh environments and function in plant defense responses. PSMs act as key components of defense-related signaling pathways and trigger the extensive expression of defense-related genes. In addition, PSMs serve as antioxidants, participating in the scavenging of rapidly rising reactive oxygen species, and as chelators, participating in the chelation of toxins under stress conditions. PSMs include nitrogen-containing chemical compounds, terpenoids/isoprenoids, and phenolics. Each category of secondary metabolites has a specific biosynthetic pathway, including precursors, intermediates, and end products. The basic biosynthetic pathways of representative PSMs are summarized, providing potential target enzymes of stress-mediated regulation and responses. Multiple metabolic pathways share the same origin, and the common enzymes are frequently to be the targets of metabolic regulation. Most biosynthetic pathways are controlled by different environmental and genetic factors. Here, we summarized the effects of environmental factors, including abiotic and biotic stresses, on PSM biosynthesis in various plants. We also discuss the positive and negative transcription factors involved in various PSM biosynthetic pathways. The potential target genes of the stress-related transcription factors were also summarized. We further found that the downstream targets of these TFs are frequently enriched in the synthesis pathway of precursors, suggesting an effective role of precursors in enhancing of terminal products. The present review provides valuable insights regarding screening targets and regulators involved in PSM-mediated plant protection in non-model plants.